An analytical model for neighbor replication on grid - Aznida Hayati Zakaria @ Mohamad (Fakulti Sains dan Teknologi, 2011)
Neighbor Replication on Grid (NRG) is one of the data replication techniques that provide high data availability and reliability in distributed database systems. However, the primary concern for the technique is not only to provide high availability and reliability but also to boost up the performance of data replication: to minimize the response times and to maximize the throughput.